The Role Of Hand Hygiene In Reducing Microorganism Contamination - Rizky Rahadian Wicaksono; Muhammad Hanif; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Hand hygiene is one of the most effective interventions in preventing the transmission of pathogenic microorganisms in healthcare facilities. The hands of healthcare workers can transmit microorganisms that cause nosocomial infections if standard hand hygiene practices are not followed. This study aimed to analyze the role of hand hygiene in reducing microbial contamination. The study used a quasi-independent design. This study used a pretest - posttest approach . The study sample consisted of 40 healthcare workers who underwent hand swab tests before and after hand hygiene measures according to WHO standards. Microorganism identification was performed through culture and Gram staining. The results showed a significant decrease in the number of microorganism colonies after hand hygiene (p < 0.05). It was concluded that hand hygiene plays an important role in reducing microorganism contamination and supporting the prevention of healthcare-associated infections.